A galectin from shrimp Litopenaeus vannamei is involved in immune recognition and bacteria phagocytosis. Issue 2 (June 2015) - Hou, Fujun; Liu, Yongjie; He, Shulin; Wang, Xianzong; Mao, Aitao; Liu, Zhigang; Sun, Chengbo; Liu, Xiaolin
Abstract Galectins are conserved family members with β-galactosides affinity that play multiple functions in embryogenesis, development and regulation of innate and adaptive immunity. However, little functional studies were reported in crustaceans. Here, a shrimp Litopenaeus vannamei galectin (LvGal) cDNA was identified with an open reading frame of 1017 bp, which encodes a putative protein of 338 amino acids. A carbohydrate recognition domain (CRD) and several amino acids residues involved in dimerization were found in LvGal. LvGal mRNA was mainly expressed in gills and hemocytes and upregulated post Vibrio anguillarum challenge. Recombinant LvGal (rLvGal) was expressed in Escherichia coli BL21 (DE3) and the purified rLvGal could strongly bind G− bacteria V. anguillarum and G+ bacteria Micrococcus lysodeikticus. Besides, rLvGal exhibited strong activity to agglutinate V. anguillarum and weak activity to agglutinate M. lysodeikticus but no obvious antibacterial activity was found with selected bacteria. In addition, in vivo experiments showed rLvGal could promote phagocytosis of bacteria by hemocytes. Thus, through these collective data we predicted LvGal is involved in immune recognition and functions as a potential pattern recognition receptor.